2021
DOI: 10.35848/1882-0786/abfca2
|View full text |Cite
|
Sign up to set email alerts
|

Pulse duration dependence of dry laser peening effects in the femtosecond-to-picosecond regime

Abstract: We found an optimum pulse duration for dry laser peening in the femtosecond-to-picosecond regime, in which the laser intensity exceeds the air breakdown threshold. A pulse duration of 1 ps produced the most effective peening effects under conditions wherein the laser energy was constant; this was caused by a decrease in the laser fluence due to a beam expansion of less than 1 ps, in addition to an increase in the thermal effect above 1 ps. When the laser intensity exceeds the air breakdown threshold, it is nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It was reported that the most compressive residual stress is induced with a pulse duration of 1.0 ps ranging from 180 fs to 10 ps using the wavelength of 1028 nm with the 1/e 2 diameter of 3.5 mm, indicating the existence of optimum pulse durations for DLP. 26 However, the influence of the pulse duration on the amount of plastic deformation, which is the direct source of peening effects, has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the most compressive residual stress is induced with a pulse duration of 1.0 ps ranging from 180 fs to 10 ps using the wavelength of 1028 nm with the 1/e 2 diameter of 3.5 mm, indicating the existence of optimum pulse durations for DLP. 26 However, the influence of the pulse duration on the amount of plastic deformation, which is the direct source of peening effects, has never been reported.…”
Section: Introductionmentioning
confidence: 99%